KD POMBOBOROS : AN INTERACTIVE LANGUAGE LEARNING MOBILE APPLICATION USING AUGMENTED REALITY AND VIRTUAL REALITY - ERRICKSON, EFFIN GUTA (Universiti Malaysia Sarawak (UNIMAS), 2020)
KadazanDusun is the largest indigenous ethnic group in Sabah with 17.8 per cent out 3.2 million populations. Although they are the largest ethnic group in Sabah, the rate of people that can speak or write in their mother tongues are declining. This is prior to the formation of Malaysia in 1963, most of the Dusun parent emphasised their children to use Bahasa Melayu and English language more than their own mother tongues. This lead to the Dusun children not acquiring their native language because they have been taught to use Bahasa Melayu and English language since their childhood. The advancement of Augmented Reality and Virtual Reality Technologies have gained vast popularity among the peoples. These technologies have completely replaced the user’s realworld environment with a simulated virtual world. Therefore, the purpose of this proposed system is to improve the ability to learn their native language by integrating Augmented Reality and Virtual Reality into the proposed application. By having this application, it is hoped that there is an increasing number of native Dusun language speaker.